Rekonstruksi Kebijakan Hukum Pidana atas Penerapan Restorative Justice Pada Tindak Pidana Umum - Eprina Mawati BR Siboro; Rahmiati Rahmiati (Jurnal Ekonomi, Bisnis dan Humaniora (EKSISHUM), 2025)
The evolution of the contemporary criminal justice system indicates a conceptual shift from a retributive paradigm towards a more restorative approach, focusing on victim rehabilitation and the restoration of social order. In the Nusantara, the implementation of Restorative Justice has gained normative grounding through a series of regulations. Nevertheless, its regulation remains fragmented within the sectoral policies of law enforcement institutions, implying potential normative disharmony and inconsistency in application, particularly in general criminal cases. This study attempts to analyze the regulations and practices of Restorative Justice within Indonesian criminal law policy, while reformulating a more integrated criminal law policy within the national criminal justice system. The research method adopted is normative juridical, encompassing legislative and conceptual approaches. Legal data, including primary, secondary, and tertiary materials, were collected through a literature review and analyzed qualitatively with deductive reasoning. Research findings indicate that although the principles of Restorative Justice have been integrated into several legal provisions, their regulation is still partial, thus a full integration within the framework of national criminal law policy has not yet been realized. Consequently, a more coherent reconstruction of criminal law policy is needed to realize an efficient, civilized, and community-restoration-oriented criminal justice system.